The influences of perforation parameters to wellbore instability and sand production - Samsuri, Ariffin; Subbiah, S. K. (1998)
This paper presents a series of laboratory experiment had been performed to see the influences of perforation parameter to wellbore instability and sand production. Shot density and perforation pattern has been varied for entire laboratory work and the stability test conducted to see the effects on the wellbore stability decreases. Whereas as the perforation pattern changes from spiral to inplane and inline the wellbore stability decreases. The sand particles produced were found by sieve analysis to be oversized 500 micron. Generally, stable perforated wellbore produced less sand particle, therefore minimizing the sand production problem.